Web-Based Expert System Application for Diagnosing Dental and Oral Diseases - Budi Kurniawan (Journal of Intelligent Decision Support System (IDSS), 2021)
Controlling the amount of inventory value is not an easy thing for Computers in the current era of globalization are a major need in supporting human work. One of the branches of computer science that is widely used by humans to help work is the formation of an expert system which is one of the sub-fields of artificial intelligence [1]. One of the uses of expert systems is in the field of dentistry. It is proven by the emergence of Nyoman Kusuma Wardna's research entitled designing an expert system for diagnosing oral and dental diseases using the CLIPS programming language which was published at the National Seminar on Information Technology Applications held at Gajah Mada University, Yogyakarta 21 June 2008 . This application appears with an interface in the form of closed questions about the symptoms felt by the user so that it does not maximize the diagnostic results obtained. This expert system is also a development of Bambang Suyono's research (National Seminar on Informatics UPN Yogyakarta 22 May 2010) which has a deficiency in using the depth first search method so that it is unable to display two or more solutions [3], whereas in diagnosing a disease sometimes a doctor determines differential diagnosis. This is what prompted the author to develop the application system by correcting all existing deficiencies. The method used in this research is Extreme Programming (XP) which is part of the AGILE method [7], consisting of five stages, namely, Planning, Design, Coding, Test and release.